Hydrocarbon biodegradation by strain BSP4 isolated from a wastewater treatment plant: insights into rhamnolipid production and characterization - Berkat, S.; Meliani, A.; Cheffi, M.; Bouassida, M.; Aliane, S.; Mazari, H. E.; Nair, S.; Meziane, M.; Sayadi, S.; Chamkha, M. (International journal of environmental science and technology (Tehran), 2025)
The present study aims to assess the environmental application potential of a rhamnolipid-producing strain, designated BSP4, from a wastewater treatment plant. BSP4 was identified with a high similarity of 99.74% by 16S rRNA sequencing as P . aeruginosa . It showed a significant potential to produce biosurfactant, namely Rhl-BSP4, on used frying oil (1%, v/v) as a low-cost substrate, yielding approximately 5.09 ± 0.91 g l −1 after 48 h of incubation. Rhl-BSP4 was capable of reducing the surface tension of water from 72 to 32 mN m ‒1 at the critical micelle concentration of 350 mg l −1 . Additionally, the performance of Rhl-BSP4 was evaluated through qualitative and quantitative tests. In fact, its stability was noted against a wide range of temperature (− 80 to 120 °C), salinity (2–12% NaCl), and pH (2–12). FTIR and NMR analyses suggested the rhamnolipid nature of the produced biosurfactant. Based on GC‒MS analyses, BSP4 degraded 97% of naphthalene (200 mg l −1 ) after seven days of incubation, with notable biodegradation of 4.82% to 83.91% of the main n -alkanes in crude oil (1%, v/v) after 21 days. Moreover, Rhl-BSP4 was more effective than the tested chemical surfactant in removing hydrocarbons from polluted soil. It also displayed promising antimicrobial activity against pathogenic strains, with minimum inhibitory concentrations ranging from 1.562 to 12.5 mg ml −1 . The results indicate that strain BSP4 is a promising hydrocarbon-degrader and rhamnolipid-producer. The efficiency of the produced biosurfactant makes it suitable for use in a range of bioremediation strategies.